Dampak Kebijakan Input, Output, dan Perdagangan Beras terhadap Diversifikasi Pangan Pokok - Setiawan, Edi; Hartoyo, Sri; Sinaga, Bonar M.; Hutagaol, M. Parulian (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2016)
EnglishAs one of the five most populous countries in the world, Indonesia has a big challenge to meet the food needs of its people. Food diversification has long been an important agenda of the national agricultural development planning program, but the achievement, however, remains disappointing. This paper aims to analyze the impacts of rice input, output and trade policy on diversification of major staple food consumption and production. This study analyzes four main staple foods, i.e. rice, maize, cassava, and wheat using national series data for the period of 1981-2013. The System of Simultaneous Equations Model consisting of 22 structural equations and 31 identity equations were estimated using a Two-Stage Least Square method. The results show that single policy instrument of reducing fertilizer and seed subsidies and increasing the government purchasing price policy increase diversification of food consumption and production. Increasing rice import tariff is not effective to improve either consumption nor production diversification, but rice import ban could improve consumption diversification. Increasing the government purchasing price is not quite effective as the compensation for the fertilizer subsidy reduction. The fertilizer subsidy reduction policy should be conducted gradually. Seed subsidy reduction combined with rice import ban is considered as an alternative to the existing policy. IndonesianSebagai salah satu dari lima negara dengan penduduk terbesar di dunia, Indonesia mempunyai tantangan cukup besar dalam pemenuhan konsumsi pangan penduduknya. Diversifikasi pangan sudah lama menjadi salah satu agenda penting dalam program nasional pembangunan pertaniani namun pencapaiannya masih jauh dari yang diharapkan. Penelitian ini bertujuan untuk menganalisis dampak kebijakan input, output, dan perdagangan beras terhadap diversifikasi produksi dan konsumsi pangan pokok yaitu, beras, jagung, ubi kayu, dan terigu, untuk data tingkat nasional tahun 1981–2013. Penelitian ini menggunakan model persamaan simultan, terdiri atas 22 persamaan struktural dan 31 persamaan identitas yang diestimasi dengan metode Two Stage Least Square (2SLS). Hasilnya menunjukkan bahwa kebijakan tunggal baik pengurangan subsidi pupuk dan benih, maupun kebijakan menaikkan Harga Pembelian Pemerintah mampu meningkatkan diversifikasi produksi dan konsumsi pangan pokok. Kebijakan tarif impor beras tidak efektif untuk meningkatkan diversifikasi konsumsi dan produksi pangan pokok, tetapi kebijakan pelarangan impor dapat meningkatkan diversifikasi konsumsi pangan. Kebijakan peningkatan harga pembelian pemerintah terbukti kurang efektif sebagai kompensasi pengurangan subsidi pupuk. Kebijakan pengurangan subsidi pupuk harus diterapkan secara bertahap. Pengurangan subsidi benih yang disertai dengan pelarangan impor dapat menjadi kebijakan alternatif saat ini.